3,4-Methylenedioxypyrovalerone (MDPV): in vitro mechanisms of hepatotoxicity under normothermic and hyperthermic conditions - Valente, Maria João (2021)
Synthetic cathinones have emerged in recreational drug markets as legal alternatives for classical amphetamines. Though currently banned in several countries, 3,4-methylenedioxypyrovalerone (MDPV) is one of the most commonly abused cathinone derivatives worldwide. We have recently reported the potential of MDPV to induce hepatocellular damage, but the underlying mechanisms responsible for such toxicity remain to be elucidated. Similar to amphetamines, a prominent toxic effect of acute intoxications by MDPV is hyperthermia. Therefore, the present in vitro study aimed to provide insights into cellular mechanisms involved in MDPV-induced hepatotoxicity and also evaluate the contribution of hyperthermia to the observed toxic effects. Primary cultures of rat hepatocytes were exposed to 0.2-1.6 mM MDPV for 48 h, at 37 or 40.5 °C, simulating the rise in body temperature that follows MDPV intake. Cell viability was measured through the MTT reduction and LDH leakage assays. Oxidative stress endpoints and cell death pathways were evaluated, namely the production of reactive oxygen and nitrogen species (ROS and RNS), intracellular levels of reduced (GSH) and oxidized (GSSG) glutathione, adenosine triphosphate (ATP) and free calcium (Ca(2+)), as well as the activities of caspases 3, 8 and 9, and nuclear morphological changes with Hoechst 33342/PI double staining. At 37 °C, MDPV induced a concentration-dependent loss of cell viability that was accompanied by GSH depletion, as one of the first signs of toxicity, observed already at low concentrations of MDPV, with negligible changes on GSSG levels, followed by accumulation of ROS and RNS, depletion of ATP contents and increases in intracellular Ca(2+) concentrations. Additionally, activation of caspases 3, 8, and 9 and apoptotic nuclear morphological changes were found in primary rat hepatocytes exposed to MDPV, indicating that this cathinone derivative activates both intrinsic and extrinsic apoptotic death pathways. The cytotoxic potential of MDPV and all the studied endpoints were markedly aggravated under hyperthermic conditions (40.5 °C). In conclusion, these data suggest that MDPV toxicity in primary rat hepatocytes is mediated by oxidative stress, subsequent to GSH depletion and increased ROS and RNS accumulation, mitochondrial dysfunction, and impairment of Ca(2+) homeostasis. Furthermore, the rise in body temperature subsequent to MDPV abuse greatly exacerbates its hepatotoxic potential.